Nuclear Reactor Engineering: Reactor Systems Engineering - Glasstone, Samuel (Springer, 2014)
This classic reference combines broad, yet in-depth coverage of nuclear engineering principles with practical descriptions of their application in the design and operation of nuclear power plants. Published in a two-volume format to accommodate readers' specific interests, the first volume concentrates on the fundamentals of nuclear engineering, while the second explores applications and more advanced topics. In the second volume, Alexander Sesonske draws on his extensive experience in nuclear engineering to investigate state-of-the-art approaches to reactor systems, including computer analysis, assisting the reader in exploiting the potential of information technology in nuclear engineering. We explore energy transport and fuel management and their roles in cost-effective plant design and operation. Sesonske discusses the environmental, health, and safety concerns that are crucial to the continued success and expansion of nuclear power, illustrating risk analysis methods that facilitate reliable assessment and control of hazards. The book also details current and potential innovations in plant design, examining challenges likely to be faced by the nuclear power industry in meeting future energy demands. investigating topics such as reactor systems, cost-effective fuel management, environmental issues, and the design of future plants